New Insights Into Cancer Chronotherapies - Jingxuan Zhou; Jingxuan Zhou; Jingxuan Zhou; Jiechen Wang; Jiechen Wang; Jiechen Wang; Xiaozhao Zhang; Xiaozhao Zhang; Qingming Tang; Qingming Tang; Qingming Tang (Frontiers Media S.A., 2021)
Circadian clocks participate in the coordination of various metabolic and biological activities to maintain homeostasis. Disturbances in the circadian rhythm and cancers are closely related. Circadian clock genes are differentially expressed in many tumors, and accelerate the development and progression of tumors. In addition, tumor tissues exert varying biological activities compared to normal tissues due to resetting of altered rhythms. Thus, chronotherapeutics used for cancer treatment should exploit the timing of circadian rhythms to achieve higher efficacy and mild toxicity. Due to interpatient differences in circadian functions, our findings advocate an individualized precision approach to chronotherapy. Herein, we review the specific association between circadian clocks and cancers. In addition, we focus on chronotherapies in cancers and personalized biomarkers for the development of precision chronotherapy. The understanding of circadian clocks in cancer will provide a rationale for more effective clinical treatment of tumors.